2014
DOI: 10.1021/om500751q
|View full text |Cite
|
Sign up to set email alerts
|

Polynuclear Phosphoramidite Copper Complexes with Mixed Trigonal/Tetrahedral Coordination in THF

Abstract: Scheme 1. Proposed Precatalytic Structures of (a) Diphosphine Copper Complexes 11 and (b) Phosphoramidite Copper Complexes 13 Note pubs.acs.org/Organometallics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Primary organocopper­(I) species are dynamic and reactive entities with a tendency to aggregate, resulting in complex mixtures of species . Here aggregation and reactivity are strongly linked to reaction outcome (yield, chemo- and enantioselectivity) and are highly dependent on solvent interactions, counterion and ligand effects, and more tractable variables such as concentration and temperature. ,,, Gschwind’s elegant work shed light on the nature of precatalytic Cu-complexes in solution using NMR spectroscopy. , …”
Section: Introductionmentioning
confidence: 99%
“…Primary organocopper­(I) species are dynamic and reactive entities with a tendency to aggregate, resulting in complex mixtures of species . Here aggregation and reactivity are strongly linked to reaction outcome (yield, chemo- and enantioselectivity) and are highly dependent on solvent interactions, counterion and ligand effects, and more tractable variables such as concentration and temperature. ,,, Gschwind’s elegant work shed light on the nature of precatalytic Cu-complexes in solution using NMR spectroscopy. , …”
Section: Introductionmentioning
confidence: 99%
“…The absolute configurations of compounds 3 were assigned to be S by analogy to 3g and 3r. Given that it is sometimes unpredictable to infer the identities of coppers peciesi ns olution from crystal structures, the solution dynamics of complex 13 was investigated using temperature-dependent 31 PNMR spectroscopy, [36] with an aim to probe into the structural integrity of the precatalyst in solution. Althoughc hiral cuprous diphosphine complexes have found broad applications in asymmetric catalysis, the structural information on the active species remains less explored, and only a few studies on the catalysis relevant structures in solution have been reported.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…In the past decades, copper­(I) complexes with nitrogen, phosphorus, and sulfur organic ligands have been extensively investigated because of their interesting structures and photochemical, photophysical properties. Copper­(I) iodide complexes, in particular, demonstrate rich photophysical behavior which could be manipulated by a wide variety of cluster chromophores [Cu n I n ] and the supporting organic ligands. With regard to N-heterocyclic organic ligands, poly­(pyridyl), , ,,, poly­(triazolyl), poly­(imidazolyl), pyrazine, poly­(pyrazolyl), and poly­(benzimidazolyl) , have been extensively employed in the assembly of the [Cu n I...…”
Section: Introductionmentioning
confidence: 99%